Protective measures against blood-borne pathogens in undergraduate students - Alva, Pilar (2006)
Objective: To measure the protective barriers use frequency by undergraduate Medical Technology School students during their elective period at both the University and the hospital. Design: Survey study. Setting: Daniel A. Carrion Tropical Medicine Institute, San Marcos Major National University. Participants: Technology Professional Academic School students. Interventions: A self-administered, anonymous questionnaire covering sex, age, and protective barriers was distributed to 68 fourth- and fifthyear medical technician students at the University of San Marcos, School of Medical Technology, Faculty of Medicine. Main outcome measures: Gown, gloves, pipete pumps and mask use. Results: Sixty-five students (95,5%) returned the questionnaire. The use of gowns, gloves, pipette pumps, and masks was 98,5%, 49,2%, 33,8% and 9,2% at the University, and 78,9%, 78,9%, 52,6% and 26,3% in the hospital, respectively. Conclusions: The use of protective barriers was low both at the University and the hospital. Study findings support a need to educate students more carefully on safe practices at work.